Analysis of the impact of rock hardness on the seismic response characteristics of CAP1400 nuclear island structure. Issue 7 (April 2020) - Li, Furong; Long, Hui; Chen, Guoxing
Abstract: With the rapid development of the nuclear power industry, appropriate sites for nuclear power plants have become a scarce resource. The construction of a nuclear power plant is subject to stringent requirements of site selection, and it is necessary to ensure that the plant will have sufficient seismic resistance. In this study, targeting the CAP1400 nuclear island structure as the research object, a three-dimensional finite element model of the dynamic interaction between the nuclear island structure and the foundation is established by considering the nonlinear characteristics of rocks using ABAQUS software. Our objective is to analyse the impact of rock hardness on the acceleration, displacement and floor response spectrum of the nuclear island structure caused by earthquake based on a total of 4 types of rock foundations with different degrees of hardness. The results show that, with the increase of rock hardness, the acceleration of the nuclear island structure increases, the displacement decreases, while the peak of floor response spectrum increases and moves towards the short period (high frequency band) direction. The seismic response of the nuclear island structure increases with the increase of elevation, and the greatest level of response is observed at the cooling water tank of the shield building, which therefore should be targeted as the key for seismic design. For rock foundations with high hardness, the seismic design for the nuclear island structure can follow the standard for rigid foundations so as to ignore the effect of the soil-structure dynamic interaction.